Spatiotemporal dynamics of attention in visual neglect: a case study. - Hillstrom, A; Husain, M; Shapiro, K; Rorden, C (2004)
Patients with visual neglect are often unaware of contralesional visual stimuli. Recent studies have demonstrated non-spatial as well as spatial deficits in allocating attention in neglect patients. We examined the spatiotemporal dynamics of directing attention in a patient with neglect for visual objects appearing in the left side of space by using a version of the attentional blink paradigm. presenting two visual stimuli in succession. The first target (T1) was presented at fixation. The location of the second target (T2) and time between the two targets was varied. When T2 appeared to the left, the patient required more time between targets to identify both accurately, compared to when T2 appeared at fixation or to the right. Our findings demonstrate a spatial and temporal gradient of attention. The results are discussed with respect to current models of visual processing in visual neglect.